UTILIZATION OF EDUCATIONAL GAMES AS INTERACTIVE LEARNING MEDIA FOR CHILDREN - Agung Triayudi; Jhiro Faran (Adisam Publisher, 2024)
This research focuses on developing educational games as interactive learning media for children, with the aim of exploring the potential of games as an effective and fun learning tool. Through a game design and development approach, this research combines educational concepts with game elements to create an interesting learning experience for children. The research methodology includes needs analysis, game design, prototype development, and user evaluation involving children as participants. The research results show that the educational games developed have succeeded in increasing children's motivation and involvement in the learning process. User evaluations show increased understanding of concepts and retention of information in children using educational games compared to traditional learning methods. In addition, feedback from children and parents indicates that the integration of game elements in learning enriches children's learning experiences, making the learning process more interactive and enjoyable. This research concludes that educational games can be used as an effective interactive learning medium for children. It is hoped that further development and application of educational games in formal and informal education contexts can provide creative and innovative alternatives in supporting children's learning processes. This research also opens up opportunities for further exploration of educational game design that adapt to children's various needs and learning styles.